Bamboo shoot fermented products alleviated DSS-induced ulcerative colitis in mice by effectively controlling inflammatory reactions and adjusting the gut microbiota and its metabolites - Lu, Xiaona; Xu, Yalin; Zhang, Cheng; Liu, Huijuan; Xie, Jiao; Tian, Bing (Frontiers in Nutrition, 2025)
BackgroundBamboo shoots have been shown to have anti-inflammatory, antioxidant, improving digestion and regulating intestinal metabolic disorders. Edible fermented foods are subject to complex reactions during the fermentation process, leading to the creation of new bioactive compounds and enzymes, which can be beneficial for the relief of symptoms of ulcerative colitis. However, research on the use of fermented bamboo shoots for alleviating ulcerative colitis symptoms is currently limited.MethodsThe effects of fermented bamboo shoots on DSS-induced UC model mice were investigated and basic physicochemical indicators, such as the levels of inflammatory factors, the composition of gut microbiota and SCFA were analysed to investigate the mechanism through which fermented bamboo shoots mitigate UC.ResultsThe results revealed that fermented bamboo shoots significantly reduced disease severity in DSS-treated mice, as evidenced by body weight recovery, a decreased disease activity index, increased colon length, and recovery from tissue damage. Fermented bamboo shoots also reduced the secretion of the proinflammatory cytokines TNF-α, IL-1β and IL-6 (p < 0.01). In addition, fermented bamboo shoots significantly increased the abundance of Akkermansia, Anaerovorax and Bacteroides in the intestines (p < 0.01), as well as the levels of SCFAs including acetic acid, propionic acid, and butyric acid in the caecum contents (p < 0.01).ConclusionIn summary, fermented bamboo shoots may play a role in restoring the composition of intestinal microbiota and the production of their metabolites, which suggests that fermented bamboo shoots may be a functional dietary supplement for alleviating UC.